Field Expansion for Homonymous Hemianopia by Mobile Application with Virtual Reality Glasses - Thitiwichienlert, Suntaree; Paenkhumyat, Nattha; Kampitak, Kosol; Tangpagasit, Wimolwan (Asian Medical Journal and Alternative Medicine, 2024)
Introduction: Homonymous hemianopia interferes with the daily living activities of patients. Objectives: To present a mobile application using the camera function in combination with three-dimensional virtual reality (VR) glasses to expand the visual field by transferring imagestoward the residual field. Methods: The authors included patients with homonymous hemianopia who could provide consent and communicate during examinations. The authors prospectively tested patients using an iOS-mobile application with a mobile camera and VR headsets to compare the binocular visual field before and after the test. Results: Six patients were included in the study. The mean age was 50 (43-57 years). We found that the patients had a range in field expansion from 0 to 39.9 degrees (average of 21.28 degrees). Five patients were satisfied with the expanded visual field in adaptive confrontation testing. Conclusions: This study has shown some effectiveness, we demonstrated a positive result of field expansion and patient satisfaction.